The atypical lipase B from Candida antarctica is better adapted for organic media than the typical lipase from Thermomyces lanuginosa. - Salis, A; Svensson, Ingemar; Monduzzi, M; Solinas, V; Adlercreutz, Patrick (Biochimica et Biophysica Acta (BBA) - Proteins and Proteomics, 2003)
Candida antarctica lipase B (CALB) and Thermomyces lanuginosa lipase (TLL) were evaluated as catalysts in different reaction media using hydrolysis of tributyrin as model reaction. In o/w emulsions, the enzymes were used in the free form and for use in monophasic organic media, the lipases were adsorbed on porous polypropylene (Accurel EP-100). In monophasic organic media, the highest specific activity of both lipases was obtained in pure tributyrin at a water activity of >0.5 and at an enzyme loading of 10 mg/g support. With tributyrin emulsified in water, the specific activities were 2780 mol min−1 mg−1 for TLL and 535 mol min−1 mg−1 for CALB. Under optimal conditions in pure tributyrin, CALB expressed 49% of the activity in emulsion (264 mol min−1 mg−1) while TLL expressed only 9.2% (256 mol min−1 mg−1) of its activity in emulsion. This large decrease is probably due to the structure of TLL, which is a typical lipase with a large lid domain. Conversion between open and closed conformers of TLL involves large internal movements and catalysis probably requires more protein mobility in TLL than in CALB, which does not have a typical lid region. Furthermore, TLL lost more activity than CALB when the water activity was reduced below 0.5, which could be due to further reduction in protein mobility.